HUBUNGAN KONSENTRASI LARUTAN BERKUMUR AIR REBUSAN BUAH MANGGIS DENGAN PERUBAHAN PH SALIVA - Bambang Sutomo; Bedjo Santoso; Irmanita Wiradona; Riski Riski (Jurnal Kesehatan Gigi, 2016)
TITLEThe relationship between concentration of mangosteen water stew as gargle and pH salivaABSTRACTCaries prevalence of people is 72.1%, with active caries prevalence of 46.5%. The incidence of dental caries due to the activity of microorganisms that leaven carbohydrates (substrate) to form acids that condition oral pH decreased to below 5. In order to maintain the pH of saliva can be done with traditional medicine, one of the mangosteen fruit. In the mangosteen fruit there is the content of alpha-mangostin and gamma-mangostin, which works as an anti-microbial. The study aims to determine the relationship between the concentration of the solution in boiling water to rinse the mangosteen fruit with changes in salivary pH.This type of research is a quasy experimental, with a design pretest-posttest design experiment. The subject of research conducted on the population that met the inclusion criteriawhich have no more than two carious tooth element and does not have gingivitis. The data analysis method is descriptive quantitative and correlation with Chi Square test.The results showed pH saliva in concentrations of 50%, before rinsing average salivary pH of 7.12 to 7.6. At a concentration of 75%, initial salivary pH was 7.2 and then changed to 8.0. Salivary pH changes after rinsing into acids derived from a concentration of 50%, whereas the increase tend to base is obtained from the concentration of 75%. The test results with the Chi square statistic obtained p.value = 0,142, and the interpretation was no relationship of the use of boiled water concentration of mangosteen to changes in salivary pH. Suggestions research results as a reference for the development of further research by conducting a more varied concentration of the solution formula to determine the right dose.  Key words : concentration mangosteen fruit stew